Report of the Committee on Economic Evaluation on New Railway Lines in the North-East Region March 1970 - Planning Commission (Planning Commission Government of India, 1979)
The Committee on Economic Evaluation of New Railway Lines in the North-East Region of India (1978) assesses the feasibility and impact of six proposed railway lines across Assam, Manipur, Tripura, Meghalaya, Nagaland, Arunachal Pradesh, and Mizoram. The report identifies the region’s underdevelopment, low per capita income, and inadequate transport infrastructure as key challenges, with road transport dominating due to difficult terrain. Using cost-benefit analysis and traffic projections through conventional and gravity models, the Committee evaluated the economic viability of the lines, estimating a total capital cost of ₹5,017 crores (1977-78 prices). While initial operating losses are projected, lines such as Lalabazar-Bairabi demonstrate high internal rates of return, indicating potential long-term benefits. The report highlights the role of these railway projects in improving regional connectivity, promoting economic integration, ensuring the supply of essential commodities, and fostering national integration. Recommendations emphasize careful planning, phased implementation, and complementary development of broader transport infrastructure to maximize socio-economic impact in the North-East.
Government of India Planning Commission
Keywords: North-East India; Railway Development; Economic Evaluation; Connectivity; Transport Infrastructure; Cost-Benefit Analysis; Traffic Forecasting; Internal Rate of Return; Regional Development; Gauhati-Burnihat; Lalabazar-Bairabi; National Integration